2008
DOI: 10.1007/s11242-008-9235-7
|View full text |Cite
|
Sign up to set email alerts
|

Coreflooding Studies to Evaluate the Impact of Salinity and Wettability on Oil Recovery Efficiency

Abstract: In this work, coreflood studies were carried out to determine the recovery benefits of low salinity waterflood compared to high salinity waterflood and the role of wettability in any observed recovery benefit. Two sets of coreflood experiments were conducted; the first set examined the EOR potential of low salinity floods in tertiary oil recovery processes, while the second set of experiments examined the secondary oil recovery potential of low salinity floods. Changes in residual oil saturation with variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 42 publications
3
46
1
Order By: Relevance
“…recovery modes (Webb et al 2005;Zhang et al 2007;Lager et al 2007;Agbalaka et al 2009) while others showed no improvement in tertiary mode (Rivet et al 2010;Nasralla et al 2011). Extensive studies have been conducted to determine the LSW recovery mechanisms, and debatable conclusions were proposed.…”
mentioning
confidence: 99%
“…recovery modes (Webb et al 2005;Zhang et al 2007;Lager et al 2007;Agbalaka et al 2009) while others showed no improvement in tertiary mode (Rivet et al 2010;Nasralla et al 2011). Extensive studies have been conducted to determine the LSW recovery mechanisms, and debatable conclusions were proposed.…”
mentioning
confidence: 99%
“…The porosity and permeability measured with water was 44.03% and 1.59 d, respectively. Figure 3 shows the schematic of the laboratory setup that is similar to the one used by Agbalaka et al (2009). It consists of a constant-flux pump (2PB-00C), high-pressure liquid accumulators for injected fluid, a cylindrical high-pressure core holder with a diameter of 2.5 cm and a length of 50 cm, and a computer for the continuous monitoring of the core injection pressure as well as the differential pressure drop across the two taps 16.7 cm apart midway along the core.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, there is extensive evidence showing that the salinity and composition of the formation water can alter wetting properties of the reservoir rock (Agbalaka et al 2009, Dumore 1964, Jerauld et al 2008, Loahardjo et al 2010, Piper and Morse 1982, Rezaeidoust et al 2009, Robertson 2009). …”
Section: Figure 1 Schematic Of the Contact Angles As Observed For A Cmentioning
confidence: 99%